Physio-chemical analysis and antioxidative response of Ag NPs synthesized by sufaid chonsa mango pulp extracts of different ripening stages - Aniqa; Zarrin Fatima Rizvi (Scientific Reports)
Abstract In this study, sufaid chonsa mango pulp aqueous extracts from different ripening stages (RS I-V) was utilized to synthesize silver nanoparticles (Ag NPs). The Ag NPs were characterized using UV-vis spectrometry, X-ray diffraction analysis (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Energy dispersice X-ray analysis (EDX). Additionally, antioxidative potential and phenolic and flavonoid-like properties of synthesized Ag NPs were also accessed. UV-vis spectrophotometer analysis showed peaks in around 400 nm. XRD analysis confirmed the crystalline structure of the green-synthesized Ag NPs, with sizes ranging from 2.11 to 11.72 nm. FTIR verified the attachment of functional groups from the mango pulp extract to the Ag NPs. SEM analyses revealed that the morphology of the Ag NPs was primarily spherical that were agglomerated. The total antioxidant capacity, measured by the DPPH assay, showed 51% radical scavenging activity for RSIII extract synthesized NPs. The highest total antioxidant capacity was observed to be 80.22 and 79.14 µg AAE/mg NPs by RSI and RSIV synthesized NPs, respectively, while the maximum total reduction potential was 28.67 µg AAE/mg for Ag NPs synthesized by RSII extract. Ag NPs derived from RSIV exhibited phenolic-like property of 70.84 µg GAE/mg, while those derived from RSII had a maximum flavonoid-like property of 35.37 µg QE/mg. This study demonstrates that mango pulp at different ripening stages produces Ag NPs with distinct characteristics, making them suitable for various environmental and biomedical applications.